2019
DOI: 10.1093/condor/duy005
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context matters when American Woodcock select singing grounds: Results from a reciprocal transplant experiment

Abstract: The multiscale nature of habitat selection during the breeding season for migratory birds means that core-use areas (e.g., breeding territories) are selected based on their local habitat features, but these may also be influenced in some way by features within a larger-scale landscape. We conducted a reciprocal transplant experiment to test the hypothesis that habitat selection and movements of male American Woodcock (Scolopax minor) in core-use areas during the breeding season depend on the perceived quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…We suspect that our initial prediction of increased gobbling activity in areas of increased male use was likely too simplistic, as wild turkeys and other similar species that use conspicuous vocalizations and displays typically select particular sites within their ranges for mate attraction (Healy 1992;Cole 2013;Brenner et al 2019). Furthermore, most gobbling activity in wild turkeys occurs around sunrise when males are at or near their roost sites (Wightman et al 2019;Wakefield et al 2020a), and roost sites are not uniformly distributed within male home ranges (Gross et al 2015;Indrani et al 2018;Wakefield et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that our initial prediction of increased gobbling activity in areas of increased male use was likely too simplistic, as wild turkeys and other similar species that use conspicuous vocalizations and displays typically select particular sites within their ranges for mate attraction (Healy 1992;Cole 2013;Brenner et al 2019). Furthermore, most gobbling activity in wild turkeys occurs around sunrise when males are at or near their roost sites (Wightman et al 2019;Wakefield et al 2020a), and roost sites are not uniformly distributed within male home ranges (Gross et al 2015;Indrani et al 2018;Wakefield et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Mate attraction is directly linked to the preference and likelihood of successfully reproducing, therefore individuals should adopt signaling strategies that maximize effective and safe communication in a dynamic environment (Lima 1998;Oseen 2002). Studies across a wide diversity of species indicate that animals alter signaling behaviors based on environmental factors, presumably to facilitate improved communication (Uy and Endler 2004;Leal and Fleishman 2004;Wilgers and Hebets 2011;Brenner et al 2019). The acoustic adaptation hypothesis posits that animals communicating vocally should adapt their vocalizations to local conditions to optimize signal transmission (Ey and Fischer 2009;Gonzalez et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, forest management for woodcock in the northeastern United States typically occurs at a larger (at least 4 km 2 ) spatial scale (Williamson 2010, Masse et al 2014) than what we found was used by towhees during the post-fledging and independence stages of their life history. Adult towhee postfledging home range sizes did not differ between HL and LL landscapes, whereas male woodcock behavior differed in these same 4 km 2 landscapes in a previous study (Brenner et al 2019). Thus, while both species utilize early-successional forests, they are likely responding to habitat features at different spatial scales (Kramer et al 2019).…”
Section: Woodcock As An Umbrella Speciesmentioning
confidence: 60%
“…Early successional forest management in these state-owned areas has focused in part on creating singing grounds, roosting fields, and nesting habitat for woodcock via forest clearcuts (Masse et al 2014). The sites where we searched for and eventually tracked Eastern Towhees were the same state-managed young forests that were selected for a separate, simultaneous study on American Woodcock habitat selection (Brenner et al 2019). We identified 6 landscapes (4 km 2 ) of 2 types: high-and low-likelihood of use by woodcock.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation